The equation of the tangent to the curve y = x2 – 2x + 7, which is parallel to the line 2x – y + 9 = 0, is |
2x – y + 3 = 0 2x – y + 6 = 0 2x – y + 1 = 0 2x – y + 4 = 0 |
2x – y + 3 = 0 |
y = x2 – 2x +7 On differentiating with respect to x, we get $\frac{dy}{dx}=2x-2$ ....(i) equation of the line 2x – y + 9 = 0 ⇒ y = 2x + 9 It's in the form of y = mx + c So, ∴ Slope of the line = 2 ....(ii) If a tangent is parallel to the line 2x – y + 9 = 0, then slope of the tangent is equal to slope of the line. ∴ 2 = 2x - 2 → from eq. (i) & (ii) 2 + 2 = 2x $4 = 2x ⇒ \frac{4}{2}=x=2$ $y=x^2-2x+7$ y = 4 - 4 + 7 = 7 Thus equation of the tangent passing through (2,7) is given by, $y - y_1 = m (x-x_1)$ $y - 7 = 2 (x - 2)$ $⇒ y-2x-3=0$ Required equation of tangent parallel to line 2x – y + 9 = 0 is y – 2x – 3 = 0 -2x + y - 3 = 0 2x - y + 3 = 0 Option 1 is correct. |